Developing Capacities for Teaching Responsible Science in the MENA Region: Refashioning Scientific Dialogue - National Research Council (The National Academies Press, 2013)
Spurred on by new discoveries and rapid technological advances, the capacity for life science research is expanding across the globe—and with it comes concerns about the unintended impacts of research on the physical and biological environment, human well-being, or the deliberate misuse of knowledge, tools, and techniques to cause harm. This report describes efforts to address dual use issues by developing institutes around the world that will help life sciences faculty learn to teach about the responsible conduct of science. Based on the successful National Academies Summer Institute for Undergraduate Biology Education and on previous NRC reports on effective methods for teaching about dual use issues, the report's authoring committee designed a general framework for the faculty institutes and chose the Middle East-North Africa (MENA) region to test a prototype faculty institute. In September 2012, the first Institute was held in Aqaba, Jordan, bringing together 28 participants from Algeria, Egypt, Jordan, Libya, and Yemen to engage with effective, evidence-based teaching methods, develop curricular materials for use in their own classrooms, and become community leaders on dual use and related topics. Developing Capacities for Teaching Responsible Science in the MENA Region: Refashioning Scientific Dialogue offers insights from the institute that will help in the design and implementation of future programs in the MENA region, and in other parts of the world.
Keywords: Biology and Life Sciences; Education; Conflict and Security Issues

The Unique U.S.-Russian Relationship in Biological Science and Biotechnology: Recent Experience and Future Directions - National Research Council (The National Academies Press, 2013)
In the fall of 2010, the U.S. National Academies (consisting of the National Academy of Sciences, the National Academy of Engineering, and the Institute of Medicine) and the Russian Academy of Sciences (in cooperation with the Russian Academy of Medical Sciences and the Russian Academy of Agricultural Sciences) initiated a joint study of U.S.-Russian bilateral engagement in the biological sciences and biotechnology (hereinafter collectively referred to as bioengagement). The U.S. Department of State and the Russian Academy of Sciences provided support for the study. The academies established a joint committee of 12 leading scientists from the two countries to assess bioengagement activities since 1996 and to provide recommendations as to collaborative efforts in the near future. The Unique U.S.-Russian Relationship in Biological Science and Biotechnology: Recent Experience and Future Directions summarizes the principal conclusions and recommendations of the study.
Keywords: Biology and Life Sciences

U.S.-Iran Engagement in Science, Engineering, and Health (2010-2016): A Resilient Program but an Uncertain Future - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
In 2010, the National Research Council published the report U.S-Iran Engagement in Science, Engineering, and Medicine (2000-2009). The review of the program described in detail the National Academies' science, technology, and health cooperation program carried out jointly with partners in Iran (otherwise known as science-engagement). The purpose of this new publication is to document the history and details of the National Academies' program of science-engagement from 2010 through 2016, while providing a perspective in considering future science-engagement. A variety of cooperative activities, and particularly workshops that dominated science-engagement during that period, are highlighted.
Keywords: Policy for Science and Technology; Health and Medicine

U.S.-Iran Engagement in Science, Engineering, and Health (2000-2009): Opportunities, Constraints, and Impacts - National Research Council (The National Academies Press, 2010)
During the first decade of the 21st century, the National Academies, working with a number of partner organizations in Iran, carried out a program of U.S.-Iran engagement in science, engineering, and health (herein referred to as science engagement). This book reviews important aspects of the science engagement program, including: (a) objectives of the program, (b) opportunities and constraints in developing the program, and (c) scientific and political impacts of the activities. Suggestions for future activities that draw on the conclusions and recommendations that have emerged from workshops and other types of interactions are set forth. Of course, the political turmoil within Iran and uncertainties as to the direction of U.S.-Iran government-to-government relations will undoubtedly complicate initiation and implementation of new science engagement activities in the near term. At the same time, many American and Iranian participants and important government officials in the United States and Iran have believed that science engagement can contribute to the evolution of an improved political environment for development of less adversarial relations between the two governments.
Keywords: Policy for Science and Technology; Health and Medicine

Understanding and Responding to Global Health Security Risks from Microbial Threats in the Arctic: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
The National Academies of Sciences, Engineering, and Medicine in collaboration with the InterAcademy Partnership and the European Academies Science Advisory Committee held a workshop in November 2019 to bring together researchers and public health officials from different countries and across several relevant disciplines to explore what is known, and what critical knowledge gaps remain, regarding existing and possible future risks of harmful infectious agents emerging from thawing permafrost and melting ice in the Arctic region. The workshop examined case studies such as the specific case of Arctic region anthrax outbreaks, as a known, observed risk as well as other types of human and animal microbial health risks that have been discovered in snow, ice, or permafrost environments, or that could conceivably exist. The workshop primarily addressed two sources of emerging infectious diseases in the arctic: (1) new diseases likely to emerge in the Arctic as a result of climate change (such as vector-borne diseases) and (2) ancient and endemic diseases likely to emerge in the Arctic specifically as a result of permafrost thaw. Participants also considered key research that could advance knowledge including critical tools for improving observations, and surveillance to advance understanding of these risks, and to facilitate and implement effective early warning systems. Lessons learned from efforts to address emerging or re-emerging microbial threats elsewhere in the world were also discussed. This publication summarizes the presentation and discussion of the workshop.
Keywords: Earth Sciences; Health and Medicine

Dual Use Research of Concern in the Life Sciences: Current Issues and Controversies - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
The potential misuse of advances in life sciences research is raising concerns about national security threats. Dual Use Research of Concern in the Life Sciences: Current Issues and Controversies examines the U.S. strategy for reducing biosecurity risks in life sciences research and considers mechanisms that would allow researchers to manage the dissemination of the results of research while mitigating the potential for harm to national security.
Keywords: Policy for Science and Technology

Indo-U.S. Workshop on Challenges of Emerging Infections and Global Health Safety: Summary of a Workshop - National Academy of Sciences (The National Academies Press, 2016)
The United States and India have pledged to deepen the linkages between their people, their businesses, and their governments for the mutual benefit of both countries and for the promotion of global peace, stability, economic growth and prosperity. Both nations are now inclined to improve relations and cooperation, but the nations need specific actions that will yield progress and build confidence and momentum for further cooperation. The Indo-U.S. Workshop on Challenges of Emerging Infections and Global Health Safety, held in November 2014, encouraged scientists from both countries to examine global issues related to emerging and existing infections and global health safety, to share experience and approaches, and to identify opportunities for cooperation to improve practice and research in these areas. This report summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine

Governance of Dual Use Research in the Life Sciences: Advancing Global Consensus on Research Oversight: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
Continuing advances in science and technology offer the promise of providing tools to meet global challenges in health, agriculture, the environment, and economic development; some of the benefits are already being realized. However, such advances have the potential to challenge the oversight systems for responsible conduct of life sciences research with dual use potential – research that may have beneficial applications but that also could be misused to cause harm. Between June 10 and 13, 2018, more than 70 participants from 30 different countries and 5 international organizations took part in an international workshop, The Governance of Dual Use Research in the Life Sciences: Advancing Global Consensus on Research Oversight, to promote global dialogue and increased common understandings of the essential elements of governance for such research. Hosted by the Croatian Academy of Sciences and Arts in Zagreb, Croatia, the workshop was a collaboration among the InterAcademy Partnership, the Croatian Academy, the Croatian Society for Biosafety and Biosecurity, and the U.S. National Academies of Sciences, Engineering, and Medicine. This publication summarizes the presentations and discussions from the workshop.
Keywords: Biology and Life Sciences

Cooperative Threat Reduction Programs for the Next Ten Years and Beyond: Proceedings of a Symposium–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
The Cooperative Threat Reduction (CTR) Program was created by the United States after the dissolution of the Soviet Union to provide financial assistance and technical expertise to secure or eliminate nuclear weapons delivery systems; warheads, chemical weapons materials, biological weapons facilities, and nuclear, biological, and chemical weapons technology and expertise from the vast Soviet military complex. In a 2009 report, Global Security Engagement: A New Model for Cooperative Threat Reduction, the National Academy of Sciences (NAS) recommended adoption of a modified approach to thinking about CTR, including the expansion of CTR to other countries and specific modifications to CTR programs to better address the changing international security environment. On September 18-19, 2017, the NAS held a symposium to discuss the state of CTR and the future of CTR programs over the next 10 years and beyond. More than 120 participants and speakers met to share experience gained implementing CTR and to explore CTR in light of new developments in science and technology, such as the convergence of chemistry and biology, the life-sciences revolution, and the needs and interests of the scientific communities in different countries. Participants also considered how government CTR programs should change and/or be reframed for the current and evolving global security and international political environment, as well as domestic requirements for impact and accountability. This publication summarizes the presentations and discussions from the workshop.
Keywords: Conflict and Security Issues

The Convergence of Infectious Diseases and Noncommunicable Diseases: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
On June 11 and June 12, 2019, the National Academies convened a workshop to explore the growing understanding of how the interplay between humans and microbes affects host physiology and causes noncommunicable diseases. Discussions included an overview of colliding epidemics, emerging research on associations between infectious and noncommunicable diseases, risks posed by chronic diseases to the development and severity of infectious diseases, and the influence of the microbiome. Workshop participants also examined the challenges and opportunities of convergence, the integration of health care delivery models and interventions, potential approaches for research, policy, and practice in the immediate-term, and potential directions for the long-term. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine

Global Infectious Disease Surveillance and Detection: Assessing the Challenges–Finding Solutions: Workshop Summary - Institute of Medicine (The National Academies Press, 2007)
Early detection is essential to the control of emerging, reemerging, and novel infectious diseases, whether naturally occurring or intentionally introduced. Containing the spread of such diseases in a profoundly interconnected world requires active vigilance for signs of an outbreak, rapid recognition of its presence, and diagnosis of its microbial cause, in addition to strategies and resources for an appropriate and efficient response. Although these actions are often viewed in terms of human public health, they also challenge the plant and animal health communities. Surveillance, defined as "the continual scrutiny of all aspects of occurrence and spread of a disease that are pertinent to effective control", involves the "systematic collection, analysis, interpretation, and dissemination of health data." Disease detection and diagnosis is the act of discovering a novel, emerging, or reemerging disease or disease event and identifying its cause. Diagnosis is "the cornerstone of effective disease control and prevention efforts, including surveillance." Disease surveillance and detection relies heavily on the astute individual: the clinician, veterinarian, plant pathologist, farmer, livestock manager, or agricultural extension agent who notices something unusual, atypical, or suspicious and brings this discovery in a timely way to the attention of an appropriate representative of human public health, veterinary medicine, or agriculture. Most developed countries have the ability to detect and diagnose human, animal, and plant diseases. Global Infectious Disease Surveillance and Detection: Assessing the Challenges—Finding Solutions, Workshop Summary is part of a 10 book series and summarizes the recommendations and presentations of the workshop.
Keywords: Health and Medicine; Conflict and Security Issues

Countering Biological Threats: Challenges for the Department of Defense's Nonproliferation Program Beyond the Former Soviet Union - National Research Council (The National Academies Press, 2009)
In response to a request from the U.S. Congress, this book examines how the unique experience and extensive capabilities of the Department of Defense (DOD) can be extended to reduce the threat of bioterrorism within developing countries outside the former Soviet Union (FSU). During the past 12 years, DOD has invested $800 million in reducing the risk from bioterrorism with roots in the states of the FSU. The program's accomplishments are many fold. The risk of bioterrorism in other countries is too great for DOD not to be among the leaders in addressing threats beyond the FSU. Taking into account possible sensitivities about a U.S. military presence, DOD should engage interested governments in about ten developing countries outside the FSU in biological threat reduction programs during the next five years. Whenever possible, DOD should partner with other organizations that have well established humanitarian reputations in the countries of interest. For example, the U.S. Agency for International Development, the Centers for Disease Control and Prevention, and the World Health Organization should be considered as potential partners.
Keywords: Conflict and Security Issues

The Biological Threat Reduction Program of the Department of Defense: From Foreign Assistance to Sustainable Partnerships - National Research Council (The National Academies Press, 2007)
This Congressionally-mandated report identifies areas for further cooperation with Russia and other states of the former Soviet Union under the Cooperative Threat Reduction (CTR) program of the Department of Defense in the specific area of prevention of proliferation of biological weapons. The report reviews relevant U.S. government programs, and particularly the CTR program, and identifies approaches for overcoming obstacles to cooperation and for increasing the long-term impact of the program. It recommends strong support for continuation of the CTR program.
Keywords: Conflict and Security Issues

Exploring Lessons Learned from a Century of Outbreaks: Readiness for 2030: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
In November 2018, an ad hoc planning committee at the National Academies of Sciences, Engineering, and Medicine planned two sister workshops held in Washington, DC, to examine the lessons from influenza pandemics and other major outbreaks, understand the extent to which the lessons have been learned, and discuss how they could be applied further to ensure that countries are sufficiently ready for future pandemics. This publication summarizes the presentations and discussions from both workshops.
Keywords: Health and Medicine

Biosecurity Challenges of the Global Expansion of High-Containment Biological Laboratories: Summary of a Workshop - National Academy of Sciences; National Research Council (The National Academies Press, 2012)
During July 10-13, 2011, 68 participants from 32 countries gathered in Istanbul, Turkey for a workshop organized by the United States National Research Council on Anticipating Biosecurity Challenges of the Global Expansion of High-containment Biological Laboratories. The United States Department of State's Biosecurity Engagement Program sponsored the workshop, which was held in partnership with the Turkish Academy of Sciences. The international workshop examined biosafety and biosecurity issues related to the design, construction, maintenance, and operation of high-containment biological laboratories- equivalent to United States Centers for Disease Control and Prevention biological safety level 3 or 4 labs. Although these laboratories are needed to characterize highly dangerous human and animal pathogens, assist in disease surveillance, and produce vaccines, they are complex systems with inherent risks. Biosecurity Challenges of the Global Expansion of High-Containment Biological Laboratories summarizes the workshop discussion, which included the following topics: Technological options to meet diagnostic, research, and other goals; Laboratory construction and commissioning; Operational maintenance to provide sustainable capabilities, safety, and security; and Measures for encouraging a culture of responsible conduct. Workshop attendees described the history and current challenges they face in their individual laboratories. Speakers recounted steps they were taking to improve safety and security, from running training programs to implementing a variety of personnel reliability measures. Many also spoke about physical security, access controls, and monitoring pathogen inventories. Workshop participants also identified tensions in the field and suggested possible areas for action.
Keywords: Conflict and Security Issues; Biology and Life Sciences

Global Health Transitions and Sustainable Solutions: The Role of Partnerships: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
On June 13–14, 2018, the National Academies of Sciences, Engineering, and Medicine convened a multistakeholder workshop to examine the transitions affecting global health and innovative global health solutions. The goal of bringing these two topics together was to collectively explore models for innovative partnerships and private-sector engagement with the potential to support countries in transition. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine

Global Security Engagement: A New Model for Cooperative Threat Reduction - National Academy of Sciences (The National Academies Press, 2009)
The government's first Cooperative Threat Reduction (CTR) programs were created in 1991 to eliminate the former Soviet Union's nuclear, chemical, and other weapons and prevent their proliferation. The programs have accomplished a great deal: deactivating thousands of nuclear warheads, neutralizing chemical weapons, converting weapons facilities for peaceful use, and redirecting the work of former weapons scientists and engineers, among other efforts. Originally designed to deal with immediate post-Cold War challenges, the programs must be expanded to other regions and fundamentally redesigned as an active tool of foreign policy that can address contemporary threats from groups that are that are agile, networked, and adaptable. As requested by Congress, Global Security Engagement proposes how this goal can best be achieved. To meet the magnitude of new security challenges, particularly at the nexus of weapons of mass destruction and terrorism, Global Security Engagement recommends a new, more flexible, and responsive model that will draw on a broader range of partners than current programs have. The White House, working across the Executive Branch and with Congress, must lead this effort.
Keywords: Conflict and Security Issues

Exploring Partnership Governance in Global Health: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
Solving the world's health challenges requires multidisciplinary collaborations that bring together the talents, experiences, resources, and ideas from multiple sectors. These collaborations in global health frequently occur through public–private partnerships (PPPs) in which public and private parties share risks, responsibilities, and decision-making processes with the objective of collectively and more effectively addressing a common goal. However, these numerous stakeholders bring varying strengths and resources to global health partnerships, but they also bring their own organizational cultures, regulations, and expectations. Managing partnerships among them is complex and requires intentional and thoughtful governance. Over the last several decades, as the number of interested stakeholders, resources invested, and initiatives launched within the global health field has grown, effective governance of global health PPPs has become increasingly critical. To explore the role of governance in PPPs for global health, the Forum on Public–Private Partnerships for Global Health and Safety convened a workshop. Participants explored best practices, common challenges, and lessons learned in the varying approaches to partnership governance. They also highlighted key issues in the governance of PPPs for global health with the goal of increasing their effectiveness in improving health outcomes. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine

Developing Norms for the Provision of Biological Laboratories in Low-Resource Contexts: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
On June 27-28, 2018, the U.S. National Academies of Sciences, Engineering, and Medicine (the National Academies) convened an international workshop in Amsterdam, the Netherlands, on developing norms for the provision of laboratories in low-resource contexts. The U.S. Department of State's Biosecurity Engagement Program requested that the National Academies organize this workshop to engage an international group of organizations that provide funding for construction, upgrades, and maintenance of biological laboratories in countries without the means to build such labs themselves. Twenty-one people from 19 organizations participated. The intent was to advance the conversation about the identification and application of guiding principles and common norms for use by these organizations in their grants, partnerships, and aid. This publication summarizes the presentations and discussions from the workshop.
Keywords: Biology and Life Sciences

Exploring Lessons Learned from Partnerships to Improve Global Health and Safety: Workshop in Brief - Institute of Medicine (The National Academies Press, 2015)
Drawing on relevant perspectives from both the private and public sectors, the Forum on Public–Private Partnerships for Global Health and Safety (PPP Forum) held a workshop on November 18–19, 2014, to explore motivations, challenges, and lessons learned during four stages of partnerships: engagement, formation, operations, and knowledge management. Workshop objectives were to engage in forward-looking multisectoral dialogue on the evolving models of partnerships for improving global health and safety; to explore opportunities for identifying and applying lessons learned from experiences of success and failure; and to discuss how the evolving model of partnerships and lessons learned can impact the future state of global health and safety, help meet global developmental challenges, and sustain improved outcomes. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine